Parental Rearing Styles, Eating Habits/behaviours and Eating Disorders Symptoms, in a Sample of Adolescents - Carvalho, Cláudia (2013)
Introduction There are few studies in the international and national literature exploring the association between parental rearing styles, eating habits/behaviours and symptoms of Eating Disorders (ED). Objectives/aims To examine the associations between the dimensions of Parental Rearing Style Questionnaire for Adolescents (EMBU-A), the dimensions of a test assessing eating disorders symptoms (Eating Attitudes Test-25/EAT-25), Body Mass Index (BMI), items assessing eating habits/behaviors and sociodemographic family and health variables; to explore which are the predictors of symptoms of eating disorders and eating habits/behaviours. Methods 402 adolescents (girls: n =241, 60%) between 12 and 18 years old (M = 14,2, SD = 1,62) answered a sociodemographic questionnaire, the EMBU-A and the EAT-25. Results We found a negative association between Emotional Support (EMBU-A), all the EAT-25 dimensions and EAT-25 total score. There was, generally, a positive association between the Overprotection and Rejection dimensions (EMBU-A) and the same results of the EAT-25. Sports’ practice was associated with a higher mean score of Motivation for Thinness and the total score of the EAT-25. In the predictive analyses, Emotional Support showed to decrease the likelihood of adolescents manifesting ED symptoms and Rejection to increase that likelihood. Conclusions Emotional Support seems to be protective of ED symptoms and dysfunctional eating habits/behaviors appearance in adolescents, while Rejection appears to increase the risk of these two outcomes. These dimensions should be worked together with parents, eventually, by psicoeducational programs. At schools and health centers, programs can be implemented to improve eating habits/behaviors and help prevent ED development